Case report of a Sertoli cell tumor with unique presentation including fevers, weight loss, and leukocytosis in a 13-year-old male - Austin G. Kazarian; Caleb Q. Ashbrook; Charles F. Timmons; Craig A. Peters; Bruce J. Schlomer (Urology Case Reports)
Sertoli cell tumors are a rare type of sex-cord stromal tumor. We present a case of a thirteen-year-old male presenting with 2–3 months of fevers and twenty-pound weight loss. Evaluation revealed leukocytosis, anemia, elevated systemic inflammatory markers and a negative infectious disease evaluation. An evaluation for malignancy revealed an incidental testicular mass. A radical orchiectomy lead to prompt resolution of fevers, leukocytosis, and elevated systemic inflammatory markers. Final pathology was consistent with a Sertoli cell tumor. To our knowledge, this is the first reported case of a Sertoli cell tumor presenting with fever, leukocytosis, and weight loss.